2021
DOI: 10.33448/rsd-v10i4.14145
|View full text |Cite
|
Sign up to set email alerts
|

Produção e caracterização físico-química de geleia de menta enriquecida com spirulina (Spirulina platensis)

Abstract: Existe uma grande preocupação com um estilo de vida mais saudável por uma parte crescente dos indivíduos. Nesse contexto, suplementos vitamínicos e alimentos enriquecidos figuram como possibilidades práticas de potencializadores nutritivos. A Spirulina Platensis apresenta alta concentração de nutrientes e é um dos mais completos suplementos naturais disponíveis na natureza.  Sendo assim, a produção de um alimento com boa aceitabilidade, como a geleia, figura como uma alternativa para suplementar a Spirulina, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…In fact, once decomposition starts, the concentration of hydrogen ions in the samples changes. According to do Bú et al (2021), acidity above 1.00% is another factor that can cause syneresis. Souza et al (2016) also found high acidity values in tamarind jelly produced from yellow passion fruit albedo with and without pectin, with the highest detected value corresponding to 1.91% of tartaric acid.…”
Section: Ph Titratable Acidity and Soluble Solid Analysesmentioning
confidence: 99%
“…In fact, once decomposition starts, the concentration of hydrogen ions in the samples changes. According to do Bú et al (2021), acidity above 1.00% is another factor that can cause syneresis. Souza et al (2016) also found high acidity values in tamarind jelly produced from yellow passion fruit albedo with and without pectin, with the highest detected value corresponding to 1.91% of tartaric acid.…”
Section: Ph Titratable Acidity and Soluble Solid Analysesmentioning
confidence: 99%
“…Even industrialized foods remain susceptible to biological activities evidenced by variations (which can be microbiological, physical, chemical, and even enzymatic), which can result in loss of nutrients, as well as physical, chemical (pH, acidity), and rheological (texture and viscosity) changes in properties [11,12]. One of the main quality attributes that influences the acceptability of jam is texture, which influences its appearance, flavor, and sensory impressions (gustatory and tactile) [13,14].…”
Section: Introductionmentioning
confidence: 99%